Pengaplikasian modul ‘ATUMICS’ pada bidang desain industri furnitur rotan - Bayu Ramadhan Wardani Edward; Mila A. Savitri; Ivonne Gabriella (Productum: Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2022)
In 1996, Adhi Nugraha, who graduated with his doctorate study from Aalto University Helsinki, Finland, created a module to make adjustments (updates) to traditional products so that they can be accepted in a contemporary context. This module is called ATUMICS (Artefact, Technique, Utility, Material, Icon, Concept, and Shape). Designers and engineers can use the module in creating a breakthrough product or system that is traditional products so that it can continue to be accepted by the modern market while maintaining the intangible values contained therein. A module can be used and practised by the RDD (Research Design Development) team in a company, especially in the product industry. This study uses interpretive qualitative analysis intending to identify ATUMICS in traditional products. The objective analysis aims to understand the elements and motivations in the ATUMICS module. With this module (ATUMICS), the author, who is also involved in the design and industry of rattan furniture products, found opportunities from the functions and benefits of the ATUMICS module. The module can help solve some actual cases in the design and industry of rattan furniture products, especially Cirebon. Especially in the area of interpretation of visual and conceptual presentations that are applicable and measurable without losing the traditional values that have been the lifeblood of rattan made products